A miniaturized alpha spectrometer for the calibration of an avalanche-confinement TEPC. (November 2017) - Bortot, D.; Pola, A.; Agosteo, S.; Pasquato, S.; Introini, M.V.; Colautti, P.; Conte, V.
Abstract: The design and development of a recent avalanche-confinement tissue equivalent proportional counter (TEPC) for microdosimetry and nanodosimetry applications required the selection of a proper miniaturized solid state detector (SSD) for detecting alpha particles emitted by a thick removable Cm-244 source embedded in the cylindrical TEPC chamber for characterization and calibration purposes. Since the available cavity for embedding the SSD detector is only 4.2 mm in diameter, no standard devices can be exploited. The selection of the best SSD for this application was based on the following requirements: very low size, proper energy resolution, cheapness. The performances of the finally selected SSD were assessed by exploiting a multi-peak calibration alpha source (Pu-239, Am-241, Cm-244). The measured energy resolution resulted about 25 keV FWHM. The TEPC calibration procedure, which exploits the selected SSD aligned to the built-in Cm-244 alpha source, is described in details. Highlights: Selection of a miniaturized SSD for energy calibration of an innovative TEPC. A compact and removable Cm-244 alpha source embedded in the TEPC sensitive volume. Coincidence technique with the SSD signal to define the alpha particles path. Assessment of TEPC calibration factors for different simulated sites and voltages.